Stabilization of Bio-Oss® particulates using photocurable hydrogel to enhance bone regeneration by regulating macrophage polarization - Wang, Jiajia; Qi, Xuanyu; Zhou, Yuqi; Wang, Guifang; Yang, Yuanmeng; Jiang, Ting; Yu, Lei; Wang, Shaoyi; Zhang, Wenjie (Frontiers in Bioengineering and Biotechnology, 2023)
Bone substitutes are widely used in maxillofacial and oral surgeries. However, in clinical practice, bone substitutes with various forms including separated particulates, powders, and blocks have exhibited poor handling properties and space maintenance characteristics, resulting in long surgery procedures and unstable volume of newly formed bone. Movable separated particulates with high stiffness have induced local inflammatory responses that hinder bone regeneration. The aim of the present study was to develop a new method to enhance the stability and operability of bone substitutes commonly used in dentistry by premixing with photocurable hydrogel-GelMA. The GelMA-encapsulated particulate had a strong capacity to aggregate separated particulates, and firmly attach to the host bone defect after photocuring compared to particulates alone. Additionally, macrophages at the surface of the GelMA-stabilized particulates tended to present a more M2-like phenotype than that of Bio-Oss®, leading to more MMR+ multinucleated giant cell formation and the induction of blood vessel invasion and new bone formation. In conclusion, this hydrogel-coated bone substitute strategy facilitates bone regeneration with increased operability, a stable volume of osteogenic space, and a favorable osteogenic microenvironment, indicating its potential value in the field of maxillofacial and oral surgeries when bone substitutes are needed.